Folk performances in Bengal Part-1 - (:unkn) unknown (My University, 2022)
The folk theatre in Bengal evolved out of the community spirit which has been existent in rural Bengal since before the sixteenth century. Genres such as the Panchaligaan(oral narrative or ballad songs) and the Kathakata(narrative) are considered predecessors of the present-day folk theatre in Bengal. Both the Panchaligaanand the Kathakatafocus primarily on religious themes and mythological stories even though with the passage of time, other socially and culturally relevant themes and subjects have also come into focus. The primary aim of these folk forms apart from the entertainment and education of the masses was to simplify and subsequently instruct through religious texts. Songs have been a dominant trait of the folk theatre in Bengal and whatever be the subject and the story of a particular performance, it is borne and carried forward by songs as well as crisp and dramatic dialogue and enunciation. Folk theatre performances are usually held during religious festivals to pay homage to gods and goddesses. In such performances, usually, there is a single narrator, and this narrator tends to represent multiple characters and as a result, multiple voices and points of view (similar in spirit to the modern-day one-man show). With the use of songs and music, these village performers have the ability to raise their narration to the level of drama. There are numerous folk theatre forms in Bengal and many of those are relevant to this day. Gambhira(also, Gambhira-gaanor naach)is a well-known form of Bengali folk theatre extremely popular in the Malda district of West Bengal. Gambhira spreads out as far as the Dinajpur and Murshidabad districts, located to the north and the south of the Malda districts respectively. It is directly linked to the Hindu festivals of Gajanand Charakwhich celebrate Lord Shiva. These festivals are generally held on the last day of Chaitra (in Aprilprior to the Bengali New Year or PoilaBoishak). Gambhiraperformances usually have two performers – one of who usually portrays the role of the village or the community Elder. The performance progresses with a dialogue between the two usually through song (and through dance in the case of Gambhiranaach). Gambhira performers not only dress up on their own but also do their own makeup. The Gambhiraperformance usually begins with a concert in which many musical instruments are played followed by an introduction known as Mukhopadwhere the performers and characters introduce themselves. The Mukhopadis followed by what is known as the Bandana or the salutation where Lord Shiva or Mahadev makes an entry (as a tribute to the Gajanand Charakfestivals). Mahadev is referred to as “nana” and he is a representative of the feudal lord (in the past) and of the government (at present). The other performers, representative of the poverty-stricken common masses are usually in soiled dhoti-s and shreds of cloth. Duets performed by a man and a woman (usually played by another man) or Charyari(an act with four characters) follow the Bandana. The most skilled actor is usually the symbol and the voice of the common masses or the underprivileged. The Gambhirausually ends with a Report which is a summation of all the significant events that have taken place in a particular year. These are usually events that are of national importance. The language of the Gambhira-gaan is a combination of various languages of West Bengal and nearby states including Bengali, Maithili, Hindi, Rajbanshi, Palia as well as dialects from the Barind tract (néeVarendra). Gambhirais truly the reflection of the zeitgeist – of the stark truth (under the guise of laughter) that dictates the lives of the ordinary toiling people of Bengal. The Gambhira-gaan of today is secular and can be held at any time of the year and has no relation to the four-day Gambhira festival which was held for four days during the Gajanand Charakfestivals. Domni or Domni-gaan is a folk theatre form popular in the West Bengal-Bihar border area, especially in Diara, Ratua, and Manikchak areas of the Malda district. Like many other Bengali folk theatre genres, Domni sees men (referred to as chakra-s orsokra-s) portray the role of female characters. Domni performances are replete with music, dance, and dialogue. However, owing to the language, which is the conversational language of the area, and incomprehensible to people outside of the community, Domni has remained restricted within the Diara area and is on the verge of extinction. The Diara area witnesses a New Year festival (also called the Sirua festival). This is the time the Domni performance groups visit affluent houses and collect fees in order to prepare for open-air Domni performances. Most Domni plays begin with the Bandanawhich first pays homage to the gods and then to the hosts. The chokra-s in the guise of women dance a Lacharior a Nachari. After the Bandana, the main body of the play starts. Serious subjects such as social oppression, injustice, marginalization, etc., all of which are of immediate social importance to the area are depicted through the means of Domniperformances. The audience of these performances is mostly the locals of the area, most of who are farmers or daily wage laborers. The Uttar and Dakshin Dinajpur areas of West Bengal are a conglomeration of various communities and classes. Together they have given rise to the folk theatre form called Khanor Khangaan (derived from the word ‘khanda’ or ‘fragments’) which is organized post-harvest. Tales of love, replete with problems are portrayed through Khan's performances. Khan's performances are unique in the sense that most of the dialogues are improvised as the performanceprogresses. Further, the pace of the dances included in these performances is usually slow. Every year, Khanperformances witness the rise of new stories based on socially relevant issues. The toiling people and the common masses of the area portray their simple lifestyle and focus on their own problems and their efforts to solve these problems through the means of Khan performances. Some of these performances see the presence of elements from religious rituals referred to as Bo-Khela amongst which HaluaHaluani (from the word ‘hal’or ‘plough’) is very popular. Dhaamor Dhaamgaan is an important folk theatre form of the Jalpaiguri district. These performances see the coming together of women dancers (also sokra), singers (locally known as gidal and Dohari), and instrumentalists. With the course of time, Dhaamperformances have taken up socially relevant themes and contemporary events and are now known as Palatia.Palatiais of three types depending on the importance of the subject: Khashpanchal, Rangpanchal, and Manpanchal. In the Cooch Behar district of North Bengal, Kushan and Dotra plays are important forms of folk theatre. Both these use the traditional Bhawaiya tune. Dotra plays usually depict popular legends or public scandals and contain themes that are secular. The burden of the play is carried by the Geedal or theMool(lead singer) whose songs are accompanied by the music of the dotara. Young girls dance to this tune. The Geedal usually wears a dhoti and a shawl and does not have any special costume. Dotra plays have a comic character called the Duaari (the local equivalent of the jester) whose role is to provide comic relief. The Duaari throughout the play regards the Geedal as his guru. Kushan plays (from the name Kush, the second son of Rama and Sita) are very popular among the Rajbanshi community of North Bengal. Kushan plays can be performed at any time of the year and are not linked to a particular festival or season.Sokra-s sing and dance to the tune of the senior bana, a bamboo instrument while the Geedal narrates the story through the medium of songduring a Kushanperformance. Some Kushan performances such as “Bishahara”(trans., “The Removal of Poison” which depicts the popular myth of the snake-goddess Manasa and Chand Sadagar, a merchant who refused to worship her, performed mostly in winter during a marriage ceremony) also sees the use of the mukhamashe, a folk flute. Kushanperformancestell the story of Rama as it is said to have been told at the court of Sri Rama in Ayodhya. Apart from this, tales from the Ramayana and the Mahabharata are portrayed in these plays. Sometimes in order to break the monotony of the play and provide dramatic relief, contemporary events (called that or khosha or phash) are brought in which have no direct link with the main play. ManasaPalapopular in South Bengal is similar in spirit to “Bishahara”. However, it is directly related to ManasaPuja, a festival celebrating the Snake goddess, Manasa, and is held during the monsoon season in the months from July to September. Manasa Pala is held at local fairs during Manasa Puja and is open to anyone who wants to attend. The Bengali folk theatre despite being a secular space does not go into deep philosophy or theory. It is a representative of the lives, thoughts, and problems of the common people of rural Bengal. Most of these folk theatre forms and the festivals which are associated with them are participated in, viewed, and celebrated by Hindus and Muslims alike without any kind of communal or religious bias.
Keywords: Panchaligaan; Religious Themes; Mythological Stories; Mythological Songs; Gajan; Charak; Mahadev; Bandana; Sokra; Bo-Khela; Bengali